Uniaxial pressure dependence of the superconducting critical temperature in RBa2Cu3O7-Î high-Tc oxides - Bud'ko, S.L. (1992)
Fil: Guimpel, J. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; University of California-San Diego. Department of Physics; Estados Unidos